Penetapan Harga Semen PT Conch dalam Praktek Jual Rugi Ditinjau dari Hukum Persaingan Usaha - Syifani Ristia Santi; Christine ST Kansil (Syntax Corporation, 2023)
The strategy of setting the selling price of a product below production costs by a business actor is an activity that is prohibited according to Law Number 5 of 1999 concerning Prohibition of Monopoly Practices and Unfair Business Competition. Determining the selling price below the cost price may indicate activities that are prohibited in Article 20 of Law Number 5 of the Year, namely the practice of selling at a loss. The practice of selling at a loss has a detrimental impact on other business actors, namely that it can eliminate business actors in the relevant market, causing an unhealthy business competition climate and leading to monopolistic practices. This is not in line with the objectives of Law Number 5 of 1999 which requires fair business competition so that it can create a healthy business climate.